Oral communication skills in the financial services and telecommunication, technology, and media industries - Sarudin, Isarji; Mohd Noor, Zainab (IACSIT Press, 2013)
The ability to speak well in English has been considered an indispensable asset, particularly in organizations that use English as the main language of communication. This paper presents the findings of a study to investigate the importance oral communication skills in the Financial Services and Telecommunication, Technology, and Media industries. Data for the study were gathered from 67 employers from the Financial Services and Telecommunication, Technology, and Media industries. The instrument to collect the data was a survey questionnaire consisted of 20 items on oral communication skills. The findings of the study, based on descriptive and inferential statistics reveal that oral communication skills were found to be statistically more important in the Financial Services than in the Telecommunication, Technology, and Media industries.